2011
DOI: 10.1007/s12273-011-0023-x
|View full text |Cite
|
Sign up to set email alerts
|

Categories of indoor environmental quality and building energy demand for heating and cooling

Abstract: Maintaining suitable indoor climate conditions is a need for the occupants' well being, while requiring very strictly thermal comfort conditions and very high levels of indoor air quality in buildings represents also a high expense of energy, with its consequence in terms of environmental impact and cost. In fact, it is well known that the indoor environmental quality (IEQ), considering both thermal and indoor air quality aspects, has a primary impact not only on the perceived human comfort, but also on the bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
0
5
0
2
Order By: Relevance
“…A Distinct comfort categories for the office room and the administration room are considered. The comfort Category II is set for the office room due to the normal level of expectation that should be used for the new buildings [76]. It corresponds to a fixed maximum indoor operative temperature limit of 26 • C. The minimum ventilation rate requirement for Category II is 1.4 l/s.m 2 .…”
Section: Zonal Comfort Criteriamentioning
confidence: 99%
“…A Distinct comfort categories for the office room and the administration room are considered. The comfort Category II is set for the office room due to the normal level of expectation that should be used for the new buildings [76]. It corresponds to a fixed maximum indoor operative temperature limit of 26 • C. The minimum ventilation rate requirement for Category II is 1.4 l/s.m 2 .…”
Section: Zonal Comfort Criteriamentioning
confidence: 99%
“…To study occupant behaviors, most of the related research defined them on the basis of occupant movements [39][40][41][42][43] and the control actions of occupants on windows, lights, air conditioning terminals and other equipment [26,[44][45][46][47][48][49][50][51]. Wang et al [40] indicated that building occupant behaviors can be broken down into two aspects: occupancy, which refers to the in-building rate; and occupants' control behaviors on building devices, including windows, doors, blinds, air conditioning terminals, lights and equipment (TVs, computers, printers, etc.).…”
Section: Definition Of the Occupant Behaviors In Buildingsmentioning
confidence: 99%
“…• a reliable dynamic simulation tool for the building energy performance analysis capable of reliably predicting the related energy demands and the indoor environmental conditions [67][68][69]; • a flexible tool to be used for the implementation of new add-on models able to suitably assess the energy performance of future building research challenges (e.g., innovative envelope integrated technologies and strategies, new energy efficiency construction materials, real users' interaction with the building indoor environmental control systems, innovative building plants, etc.) [48,70,71].…”
Section: Aim Of the Work And Content Of The Papermentioning
confidence: 99%